(untitled) (Research, Society and Development, 2022)
The right to education is assured to everyone as expressly provided for in the 1988 Constitution of the Federative Republic of Brazil. Nonetheless, as well as in many other sectors, education has suffered and still has suffered the impacts of social isolation resulting from the COVID-19 Pandemic, which found in Emergency Remote Education a way of minimizing the damage caused. Thereby, the present study aimed to analyze the effectiveness of the right to education in basic education in the State of Minas Gerais from the Emergency Remote Education adopted in the COVID-19 Pandemic. This article is a descriptive research of a quantitative-qualitative nature carried out from an integrative literature review and analysis of secondary data. From the results obtained, it was possible to observe that the effectiveness of the right to education was mitigated in the Basic Education of the State of Minas Gerais from the ERE adopted in the COVID-19 Pandemic.